DIFFERENCES IN ESTROGEN LEVELS BEFORE AND AFTER GIVING CALLANGGI TEA TO WISTAR STRAINING WHITE FEMALE RATS (RATTUS NORVEGICUS) IN MEDROXYPROGESTERONE ACETATE (DMPA) INDUCTION - Ima Syamrotul Muflihah; Tantri Analisawati; Wulan Margiana; Andi Muh Maulana (Yayasan Education and Social Center, 2023)
Data from the 2017 Indonesian Demographic and Health Survey (IDHS) show that hormonal injection contraception has been the most common choice taken by women in more than 90 countries worldwide since 1967. Hormonal contraception uses essential ingredients from synthetic hormones used to regulate pregnancy. The 3-month injection KB (Depo-medroxprogestin acetate/DMPA) has the highest rating, 46.84%. DMPA thickens the cervical mucus, interfering with the ovulation process. The affects couples of childbearing age to get offspring quickly, causing stress where women often experience anxiety, depression, and prolonged fatigue that affect hormones and female reproductive organs. Midwifery care has been carried out by combining conventional and complementary midwifery services, which have become an essential part of midwifery practice. Decree of the Minister of Health Number 1109/Menkes/Per/IX/2007 concerning Alternative Complementary Medicine. Complementary is complementary, perfecting. Complementary therapy is carried out to complement conventional medical treatment and is rational, and does not conflict with health values ​​and laws in Indonesia. There are several methods of accelerating fertility recovery, one of which is using medicinal plants as an alternative, namely clover. The community widely uses clover for daily consumption. In this study, the method used as clover in a tea preparation is to be induced orally in female Wistar rats. Clover belongs to the water spike group, which contains isoflavones, antioxidants, and anti-inflammatories. The content of isoflavones in clover leaves can balance female hormones. The results of this research are beneficial for the development of science and technology, especially complementary therapy regarding the potential of clover as a natural ingredient that helps restore fertility